(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The study was designed to analyze the antibiotic susceptibility pattern of fluoroquinolones among Salmonella enterica. Methods: A cross-sectional study was carried out at National Public Health Laboratory, Kathmandu. Blood samples were collected from suspected enteric fever patients and cultured in BACTEC standard/10 Aerobic/F culture vials. Isolates obtained from the vials with bacterial growth were identified by standard procedure. Serotyping of the identified isolates Salmonella enterica was done. An antibiotic susceptibility test was done by Kirby-Bauer disc diffusion method and results were interpreted according to Clinical Laboratory Standards Institute (CLSI 2014) guidelines. Results: Among 404 samples, 17 (4.2%) were positive for Salmonella enterica in which 9 (52.9%) were Salmonella Typhi and 8 (47.1%) were Salmonella Paratyphi A. All the Salmonella isolates showed resistance to nalidixic acid and ampicillin and showed sensitivity to ceftriaxone and chloramphenicol. No multi-drug resistant isolates were identified in this study. All isolates of Salmonella Typhi and Salmonella Paratyphi A showed the reduced susceptibility to ciprofloxacin and ofloxacin. Conclusion: It is concluded that fluoroquinolones cannot be considered as the drug of choice for the treatment of Salmonella infections due to their high level of reduced susceptibility and resistance to fluoroquinolones and third generation cephalosporin antibiotics like ceftriaxone remains better choice of drugs against fluoroquinolone-resistant Salmonella Typhi and Paratyphi.